Characterization of Khlong Marui Fault Zone using seismic reflection and shear-wave velocity profiles: Case study in Khiriratnikhom district, Surat Thani province, southern Thailand - Sawasdee Yordkayhun (Science Faculty of Chiang Mai University, 2020)
Detailed fault mapping and characterization are important for seismic hazard assessment. The Khlong Marui Fault Zone (KMFZ) is a major active strike-slip fault system in southern Thailand. It extends in a southwest-northeast direction from Phuket towards Surat Thani province. Although the general fault system can be identified from surface observations, investigation of the fault zone in Surat Thani province is challenging because the surface expression is not obvious and thick sediments cover the area. Therefore, shallow seismic reflection profiles were acquired in the Khiriratnikhom district, Surat Thani province. The aims of this study were to characterize the subsurface geological structures in the vicinity of the fault zone. For the seismic data analysis, conventional data processing such as data editing, static correction and frequency filtering are effective in enhancing signal to noise ratio of stacked section. However, detailed geological information at shallow levels in the subsurface are not well imaged due to the effects of data acquisition and processing. To address this limitation, seismic reflection and shear wave velocity (Vs) profiles were obtained from multichannel analysis of surface waves (MASW) and are jointly interpreted. The results show a sequence of subsurface boundaries extending from the surface to a depth of about 250 m. The variations in seismic velocities and vertical offset of the main horizon are the fault signature observed on seismic sections and in the shear wave velocity fields. The results coincide well with the fault strike obtained from a previous geophysical interpretation. This finding suggests the possibility of ongoing activity of the KMFZ.